Movement, survival, and home range size of translocated american martens (Martes americana) in Wisconsin - James E. Woodford; David M. MacFarland; Mike Worland (Wildlife Society Bulletin, 2013)
ABSTRACT We translocated and released a total of 90 (55 F and 35 M) wild American martens (Martes americana) from Minnesota to northern Wisconsin, USA, during 2008–2010. Our objective was to evaluate the short‐term results of this translocation project by comparing marten dispersal, time to residency, and survival by release method, sex, and age categories. On average, translocated martens took 18 days (range = 1–64 days) and traveled 4.6 km (range = 0.4–45.7 km) from release sites before establishing residency. Although survival probabilities for adults and males were 0.84 and 0.79 and juveniles and females were 0.66 and 0.71, respectively, they were not statistically different. Translocated adult and juvenile survival was similar to resident adult and juvenile survival reported in Wisconsin and elsewhere. Predation (primarily by other carnivores) was the main cause (85%) of observed mortality for translocated animals, but it did not appear to be a major limiting factor for adults or juveniles. Contrary to some studies, we found no significant difference between release methods for any analyzed parameter, but we observed increased injuries to slow‐released individuals. We concluded there was no benefit resulting from slow‐release or an acclimation period for translocation of American martens and that long‐term monitoring of the population is needed to evaluate species recovery in Wisconsin. © 2013 The Wildlife Society.